Cryptate complexes with the potential for CO2 activation: quantum chemical predictions and synthetic efforts - Fuchs, Alexander; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2012)
In this work we discuss the possibility of CO2 activation by novel magnesium and zinc cryptate complexes. The choice of the complexes is partially based on the results of studies on CO2 fixation by amidometal complexes and partially inspired by the mode of action of the RuBisCO enzyme. Quantum chemical calculations underline the potential of this new approach, and argue for reversible CO2 activation and bonding to the cryptand complexes. We then report on the first steps towards an experimental realization and its limitations. A new cryptand molecule (15-oxa-1,4,7,10-tetraazabicyclo[5.5.5]heptadecane) was synthesized featuring two secondary amino functions. It was shown to give stable complexes with lithium and zinc ions, in which the metal ions are captured inside the cryptand void. Unfortunately, the last step in the preparation of the targeted complex for CO2 fixation, namely deprotonation of both secondary amino groups, was not achieved.